Captive Audience Scenarios in Ethiopia: Some Observations - Wakene, Wondwossen Frew (Bahir Dar University Journal of Law, 2022)
Captive audience situations are conditions in which someone is exposed to speech that he does not want to listen to and speech that is contrary to his foundational beliefs. Captive auditory scenarios are pervasive; we encounter these in our daily routines. We find these situations in workplaces, taxis and buses, cafés, and on cell phones and TVs, to mention a few. Keeping aside their pervasiveness in our daily lives, captive audience situations entangle our basic freedoms like freedom of expression and freedom of religion and beliefs. Captive audience speeches have their own protagonists and detractors. While some argue that they are expressions and so demand basic protection, others hold that foundations of freedom of expression do not support them at all.This article depicts the concept of captive audience, analyzes the Ethiopian experience at the backdrop of comparative experience and concludes that captive audience situations are in the making in Ethiopia and the laws are not as such full-fledged enough to protect individuals. It then concludes that captive audience situations need to be clearly addressed on the face of religious extremism and intrusive and irresponsible expressions encountered on a daily basis.